2008
DOI: 10.1128/aac.01420-07
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Genetic Markers of Drug Resistance and Susceptibility Profile of Clinical Neisseria gonorrhoeae Strains

Abstract: The main goal of this work is to clarify the predictive value of known genetic markers of Neisseria gonorrhoeae resistance to penicillin, tetracycline, and fluoroquinolones. The correlation between the presence of certain genetic markers and susceptibility of N. gonorrhoeae isolates to penicillin, tetracycline, and fluoroquinolones has been analyzed by means of statistical methods. Susceptibility testing with penicillin, tetracycline, and fluoroquinolones was performed by the agar dilution method. N. gonorrhoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…Thus, for our study, nucleic acid extraction was performed directly from specimens submitted for Aptima testing and from suspensions of cultures prepared in saline using the QIAamp DNA minikit. These extracts were used for amplification and sequencing of the penA, por, and tbpB gene targets performed using previously described primers (7,16,17) for direct molecular characterizations. In a preliminary pilot study, mutations in the ponA gene, coding for PBP 1, pilQ coding for the pilus secretin protein, bla TEM-1 coding for ␤-lactamase, and the Mtr promoter and repressor regions in addition to the penA, por, and tbpB genes were also monitored using samples with elevated cefixime MIC values; however, a reproducible association was found between changes in penA, por, and tbpB and decreased susceptibility for the limited number of samples tested in this study (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for our study, nucleic acid extraction was performed directly from specimens submitted for Aptima testing and from suspensions of cultures prepared in saline using the QIAamp DNA minikit. These extracts were used for amplification and sequencing of the penA, por, and tbpB gene targets performed using previously described primers (7,16,17) for direct molecular characterizations. In a preliminary pilot study, mutations in the ponA gene, coding for PBP 1, pilQ coding for the pilus secretin protein, bla TEM-1 coding for ␤-lactamase, and the Mtr promoter and repressor regions in addition to the penA, por, and tbpB genes were also monitored using samples with elevated cefixime MIC values; however, a reproducible association was found between changes in penA, por, and tbpB and decreased susceptibility for the limited number of samples tested in this study (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…N. gonorrhoeae clinical isolates collected in different regions of Russia from 2004 to 2005 were obtained from the Central Research Institute of Dermatology and Venereology. All isolates were identified as N. gonorrhoeae and tested for serotype and for susceptibility to penicillin G (PEN), tetracycline (TET), ciprofloxacin (CIP), spectinomycin, and ceftriaxone as a part of a previous investigation (11).…”
Section: Methodsmentioning
confidence: 99%
“…In Russia, strains that are resistant to penicillin, tetracycline, and fluoroquinolones are common, reaching up to 60% prevalence in some regions (14). As is generally known, most resistance mechanisms in N. gonorrhoeae are linked to mutations in genomic DNA, and a wide dissemination of such mutations has been demonstrated in subjects with gonorrhea in the Russian population (11). In fact, chromosomally mediated drug resistance expands clonally in a bacterial population.…”
mentioning
confidence: 99%
“…Unfortunately, no commercially available gonococcal NAATs detect any AMR determinants. However, in-house molecular assays exist for detection of one or more genetic AMR resistance determinants involved in plasmid-mediated penicillin resistance (29)(30)(31), chromosomally mediated penicillin resistance (26,(32)(33)(34)(35), plasmid-and chromosomally mediated tetracycline resistance (36), resistance to macrolides (32, 37-42), fluoroquinolone resistance (43-49), ESC resistance (50)(51)(52)(53), and multidrug resistance (54)(55)(56). Unfortunately, for most AMR determinants, the sensitivity and specificity of these molecular AMR assays for determination of AMR are often low.…”
Section: Detection Of Antimicrobial Resistance In N Gonorrhoeaementioning
confidence: 99%